2011
DOI: 10.1371/journal.pone.0026461
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Zebrafish M6Ab at Serine 263 Contributes to Filopodium Formation in PC12 Cells and Neurite Outgrowth in Zebrafish Embryos

Abstract: BackgroundMammalian M6A, a member of the proteolipid protein (PLP/DM20) family expressed in neurons, was first isolated by expression cloning with a monoclonal antibody. Overexpression of M6A was shown to induce filopodium formation in neuronal cells; however, the underlying mechanism of is largely unknown. Possibly due to gene duplication, there are two M6A paralogs, M6Aa and M6Ab, in the zebrafish genome. In the present study, we used the zebrafish as a model system to investigate the role of zebrafish M6Ab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
(62 reference statements)
2
12
0
Order By: Relevance
“…The phosphorylation state of M6a at Y251 seems not to be involved in the formation of filopodia-like processes in hippocampal neurons. In agreement with these findings, phosphorylation at Ser263 of the M6azebrafish ortholog M6Ab promotes filopodia formation, but not neurite extension, in PC12 cells (Huang et al, 2011). Moreover, M6a lacking intracellular phosphorylation sites for casein-kinase 2, and protein PKC-expressing neurons bore filopodia, but the motility of the protrusions was slow compared with that of M6a wt .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The phosphorylation state of M6a at Y251 seems not to be involved in the formation of filopodia-like processes in hippocampal neurons. In agreement with these findings, phosphorylation at Ser263 of the M6azebrafish ortholog M6Ab promotes filopodia formation, but not neurite extension, in PC12 cells (Huang et al, 2011). Moreover, M6a lacking intracellular phosphorylation sites for casein-kinase 2, and protein PKC-expressing neurons bore filopodia, but the motility of the protrusions was slow compared with that of M6a wt .…”
Section: Discussionsupporting
confidence: 74%
“…Accordingly, we found that the structure of EC2 is critical to induce filopodium outgrowth and synaptogenesis (Fuchsova et al, ) and that mutations in M6a intracellular sites, which are motifs for protein kinase C (PKC) and casein kinase‐2 phosphorylation, decrease the motility of filopodia induced by M6a (Brocco et al, ). The zebrafish M6a ortholog, which lacks a phosphorylation site for PKC, fails to induce neurite extension in PC12 cells (Huang et al, ). Also, M6a depends on membrane lipid microdomain association and requires the activity of Src kinases and mitogen‐activated protein kinases (MAPK) for its filopodium induction (Scorticati et al, ).…”
mentioning
confidence: 99%
“…M6a is a membrane glycoprotein encoded by the gene GPM6A. M6a, together with M6b, proteolipid protein (PLP) and DM20, belongs to the PLP family, and has been related to neuronal plasticity in different experimental models (Lagenaur et al 1992;Alfonso et al 2005;Michibata et al 2009;Huang et al 2011;Sato et al 2011a;Zappia et al 2012). M6a positively contributes to neuritogenesis, filopodia outgrowth and synapse formation in M6a-over-expressing neurons, but its mechanism of action remains unknown (Alfonso et al 2005;Fuchsova et al 2009;Formoso et al 2015).…”
mentioning
confidence: 99%
“…The 293T cells were maintained at 37 °C in minimal essential medium-alpha medium, 10 % fetal bovine serum, 100 mg/ml streptomycin, and 100 U/ml penicillin. Plasmid transfection and cell collection were done with standard procedures as described previously [67]. Transfected 293T cells collected from one 6-well plate were lysed in 0.1 ml immunoprecipitation lysis buffer (150 mM NaCl, 20 mM HEPES (pH 7.2), 10 mM NaF, 1 mM EDTA, 0.5 % NP-40, 1 mM Na3VO4, 1 mM PMSF, and 1 mM DTT), then sonicated for 10 s three times using a UP50H machine at an 80 % power level (Dr. Hielscher, Teltow, Germany).…”
Section: Methodsmentioning
confidence: 99%